Characterization of the human lipoprotein lipase (LPL) promoter: evidence of two cis-regulatory regions, LP-alpha and LP-beta, of importance for the differentiation-linked induction of the LPL gene during adipogenesis. - Enerbäck, S (1992)
When preadipocytes differentiate into adipocytes, several differentiation-linked genes are activated. Lipoprotein lipase (LPL) is one of the first genes induced during this process. To investigate early events in adipocyte development, we have focused on the transcriptional activation of the LPL gene. For this purpose, we have cloned and fused different parts of intragenic and flanking sequences with a chloramphenicol acetyltransferase reporter gene. Transient transfection experiments and DNase I hypersensitivity assays indicate that several positive as well as negative elements contribute to transcriptional regulation of the LPL gene. When reporter gene constructs were stably introduced into preadipocytes, we were able to monitor and compare the activation patterns of different promoter deletion mutants at selected time points representing the process of adipocyte development. We could delimit two cis-regulatory elements important for gradual activation of the LPL gene during adipocyte development in vitro. These elements, LP-alpha (-702 to -666) and LP-beta (-468 to -430), contain a striking similarity to a consensus sequence known to bind the transcription factors HNF-3 and fork head. Results of gel mobility shift assays and DNase I and exonuclease III in vitro protection assays indicate that factors with DNA-binding properties similar to those of the HNF-3/fork head family of transcription factors are present in adipocytes and interact with LP-alpha and LP-beta. We also demonstrate that LP-alpha and LP-beta were both capable of conferring a differentiation-linked expression pattern to a heterolog promoter, thus mimicking the expression of the endogenous LPL gene during adipocyte differentiation. These findings indicate that interactions with LP-alpha and LP-beta could be a part of a differentiation switch governing induction of the LPL gene during adipocyte differentiation.